Avaliação de software educacional para ensino aprendizagem de Inglês para a escola pública: coletando subsídios avaliativos - Maggioli, Denise Lage (2007)
This research is a result of the concerns I had as a professional in education related to the evaluation of didactic material, which nowadays include not only printed material but also material connected to technology, such as softwares and online courses. This research aims at evaluating an educational software recommended to be used at the public schools of Ensino Fundamental e Médio, considering the paradigms presented in the Parâmetros Curriculares Nacionais Língua Estrangeira. The theoretical basis for this research were the Parâmetros Curriculares Nacionais -Lingua Estrangeira (Brasil, 1998) and Parâmetros Curriculares Nacionais Ensino Médio (Brasil, 1999), used as a reference by the teacher in his or her classroom, the lines of thinking in psychology that were used as basis for the teaching and learning theories that have had most influence in the teaching and learning process of foreign language in our culture (Williams & Burden, 1997; Rego, 2004; Vygotsky, 1993,2003), the language description theories (Graddol, 1994; Hutchinson & Waters 1987; Bloor & Bloor, 1995), considerations on didactic material (Cunningsworth, 1984, 1995; Tomlinson, 1998; Graves, 2000), the definition of task according to Ellis (2003), software evaluation criteria (Squires & McDougall, 1997; Stirling, 1998; Alagumali & Anderson, 1997) and the evaluation criteria for didactic material by Ramos (1998) and Freire et al. (2004). This research has shown that, although the language description theories and the teaching and learning theories that constitute the software do not match the educational paradigms in force nowadays, according to the Parâmetros Curriculares Nacionais Língua Estrangeira (Brasil, 1998) and the Parâmetros Curriculares Nacionais Ensino Médio (Brasil, 1999), from a technological point of view the software presents resources that can help both teachers and students in the teaching and learning process of a foreign language